Fathers of children with a disability: health, work, and family life issues. Issue 16 (31st July 2022) - Bourke-Taylor, Helen M.; Cotter, Claire; Joyce, Kahli S.; Reddihough, Dinah S.; Brown, Ted
Abstract: Purpose: Fathers in families raising children with disabilities are under-researched. Fathers' perspectives can be better accommodated in childhood disability services that operate on a family-centred paradigm if their perspectives are understood. This study aimed to investigate the perspectives of fathers on caring and family life, work, and health. Methods: A mixed-methods design with an online questionnaire included open-ended questions and three instruments: Depression Anxiety Stress Scales (DASS); Health Promoting Activities Scale (HPAS-M); Fathers of Children with Developmental Challenges (FCDC) Scale. Results: Fathers ( n = 33) reported high depressive (58%), anxiety (37%), and stress symptoms (61%). Fathers reported low participation in health-promoting activity with less than weekly: planning health activities (58%); solo physical activity (26%); social activity (3%); time relaxing (16%). Sixty-four percent worked full-time, although work was reported to be challenged by family responsibilities. Fathers described directly caring for their children although service interactions were low and delegated to mothers. Conclusions: Fathers in this study reported stress, mental health issues, and low participation in healthy activity. Fathers experienced challenges related to career progression and job choices due to family responsibilities. Providing individualised and responsive support to fathers of a child with a disability would better support the family unit. IMPLICATIONS FOR REHABILITATION: Fathers of children with a disability in this study experienced high mental health symptoms. Fathers were involved with their child's care at home but had low service interactions suggesting that service providers need to discover new ways to better engage fathers. Fathers experienced challenges to participation in paid work secondary to care responsibilities for their child with a disability and resulting needs of their family. Services that better support fathers are important to promote better health and wellbeing and support families.